2020
DOI: 10.3389/fcell.2020.604896
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the JAK2-STAT5 Pathway by Signaling Molecules in the Mammary Gland

Abstract: Janus kinase 2 (JAK2) and signal transducers and activators of transcription 5 (STAT5) are involved in the proliferation, differentiation, and survival of mammary gland epithelial cells. Dysregulation of JAK2-STAT5 activity invariably leads to mammary gland developmental defects and/or diseases, including breast cancer. Proper functioning of the JAK2-STAT5 signaling pathway relies on crosstalk with other signaling pathways (synergistically or antagonistically), which leads to normal biological performance. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 113 publications
0
23
0
Order By: Relevance
“…In order to nominate key genes and factors that might be responsible for pathway-level changes in these two subclusters, we looked at the expression of key regulators that were differentially expressed with time postpartum, including those important for hormone signaling, growth factor signaling, AP-1 signaling, factors involved in STAT5 signaling, and several milk production component genes ( Fig. 5 C ) ( 55 57 ). We found that the expression of several hormone receptor genes changed in opposite directions with time in the LC1 and secretory lactocyte subclusters, with estrogen receptor ( ESR1 ) and prolactin receptor ( PRLR ) increased in secretory lactocytes and decreased in LC1 cells.…”
Section: Resultsmentioning
confidence: 99%
“…In order to nominate key genes and factors that might be responsible for pathway-level changes in these two subclusters, we looked at the expression of key regulators that were differentially expressed with time postpartum, including those important for hormone signaling, growth factor signaling, AP-1 signaling, factors involved in STAT5 signaling, and several milk production component genes ( Fig. 5 C ) ( 55 57 ). We found that the expression of several hormone receptor genes changed in opposite directions with time in the LC1 and secretory lactocyte subclusters, with estrogen receptor ( ESR1 ) and prolactin receptor ( PRLR ) increased in secretory lactocytes and decreased in LC1 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Prolactin is a key hormone regulating milk protein synthesis in mammals [49]. In bovine mammary epithelial cells, prolactin activates STAT5 phosphorylation via the prolactin receptor, promotes the expression of β-casein gene and maintains cell proliferation and milk protein synthesis [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…STAT5A is a core lactational gene that is involved in proliferation, cell survival, and milk component synthesis. 70,80,[82][83][84][85][86] Interestingly, we observe decreases in STAT5a/b expression and downstream targets such as AKT1 72 , ACACA (a gene involved in fatty acid synthesis), and CSN2 (the gene encoding beta-casein) over the course of lactation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to nominate key genes and factors that might be responsible for pathwaylevel changes in these two sub-clusters, we looked at the expression of key regulators that were differentially expressed with time postpartum, including those important for hormone signaling, growth factor signaling, AP-1 signaling, factors involved in STAT5 signaling, and several milk production component genes (Figure 5D) [70][71][72] . We found that the expression of several hormone receptor genes changed in opposite directions with time in the LALBA low epithelial and secretory lactocyte sub-clusters, where estrogen receptor (ESR1) and prolactin receptor (PRLR) increased in secretory lactocytes and decreased in LALBA low epithelial cells.…”
Section: Ementioning
confidence: 99%